Radiogram from Anny van der Sluys to Max Bredig, July 5, 1945 - Van der Sluys, Anny (1945)
Anny van der Sluys tells Max Bredig (1920-1977) that she has not heard from Alfred (1900-1944) and Eva Schnell (1913-1944). Alfred Schnell was a former colleague of Max Bredig. In the early 1940s, Alfred and his wife Eva fled to The Hauge to escape the persecution of the Jewish people in Germany. In 1943, German forces invaded the Netherlands and the Schnells went into hiding. They were murdered by Dutch soldiers loyal to the Third Reich in 1944.
Keywords: Radio Corporation of America; Bredig, Max Albert, 1902-1977; Van der Sluys, Anny; Schnell, Eva, 1913-1944; Schnell, Alfred, 1900-1944